THE FORM AND MEANING OF IDIOMS IN ONLINE NEWS OPINION COLUMNS OF NARASI TV - Devia; Herpindo; Jendriadi (JURNAL KONFIKS, 2026)
This study is motivated by the use of idioms in TV Narrative opinions, which causes its own problems because not all readers have the same understanding of the idioms used. The author uses idioms in opinions as a form of expression to convey his opinion. Idioms are also used to shorten the text so that it is more concise and straightforward. This study aims to define two forms of idioms, namely idioms based on their level of connection and their constituent elements, as well as to explain their meanings so that they can be understood by readers. This study uses a descriptive qualitative approach with data collection using the observation and note-taking methods. Then, the analysis technique applies the method from Miles and Huberman. The data sources used for this study are based on 16 online opinion articles from Narasi TV. The results show that out of 16 opinion articles, 14 articles contain idiomatic expressions with a total of 22 expressions. Of the 22 idioms found, based on their level of attachment, there were 6 full idioms and 16 partial idioms. Meanwhile, based on their constituent elements, there were 6 body name idioms, 1 color idiom, 2 animal name idioms, and 13 word class idioms. The findings show that idioms and word class idioms are widely used in Narasi TV opinion articles. This indicates that Narasi TV opinion writers want to convey criticism and messages using language that is interesting but still understandable to readers. This research can contribute to the study of idiom semantics in the realm of online news opinion media, which is currently still limited.